Finite Time Path Field Theory and a New Type of Universal Quantum Spin Chain Quench Behavior - Domagoj Kuić; Alemka Knapp; Diana Šaponja-Milutinović (Universe, 2025)
We discuss different quench protocols for Ising and XY spin chains in a transverse magnetic field. With a sudden local magnetic field quench as a starting point, we generalize our approach to a large class of local non-sudden quenches. Using finite time path field theory (FTPFT) perturbative methods, we show that the difference between the sudden quench and a class of quenches with non-sudden switching on the perturbation vanishes exponentially with time, apart from non-substantial modifications that are systematically accounted for. As the consequence of causality and analytic properties of functions describing the discussed class of quenches, this is true at any order of perturbation expansion and thus for the resummed perturbation series. The only requirements on functions describing the perturbation strength switched on at a finite time <semantics>t=0</semantics> are as follows: (1) their Fourier transform <semantics>f(p)</semantics> is a function that is analytic everywhere in the lower complex semiplane, except at the simple pole at <semantics>p=0</semantics> and possibly others with <semantics>ℑ(p)<0</semantics>; and (2) <semantics>f(p)/p</semantics> converges to zero at infinity in the lower complex semiplane. A prototypical function of this class is <semantics>tanh(ηt)</semantics>, to which the perturbation strength is proportional after the switching at time <semantics>t=0</semantics>. In the limit of large <semantics>η</semantics>, such a perturbation approaches the case of a sudden quench. It is shown that, because of this new type of universal behavior of Loschmidt echo (LE) that emerges in an exponentially short time scale, our previous results for the sudden local magnetic field quench of Ising and XY chains, obtained by the resummation of the perturbative expansion, extend in the long-time limit to all non-sudden quench protocols in this class, with non-substantial modifications systematically taken into account. We also show that analogous universal behavior exists in disorder quenches, and ultimately global ones. LE is directly connected to the work probability distribution, and the described universal behavior is therefore appropriate in potential concepts of quantum technology related to spin chains.